Communicative Language Teaching (CLT) through Role Play and Task-Based Instruction - Kartini Rahmatillah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2019)
This research focuses on several aims, first whether Communicative Language Teaching (CLT) through Role Play and Task Based Instruction best implemented in English learning process in STIE Madani Balikpapan.Second it aims to prove whether Communicative Language Teaching (CLT) can improve students’ English skill based on TOEFL score. Third, it aims to find out students’ perception about the implementation of Communicative Language Teaching (CLT) in English learning process in STIE Madani Balikpapan.It is a combination of quantitative and qualitative research in which survey, experiment, and interview are done related to the aims of the research. The sample is 37 students from two classes that took English Practice/TOEFL subject in academic year of 2019-2020. The result stated that Communicative Language Teaching (CLT) is best implemented through role play and task based instruction.CLT helps students to better achieve their TOEFL score since there is an increase between the pretest and the post-test. Through the use of Communicative Language Teaching (CLT) approach in class, students feel they have interest more in learning English, do not feel afraid in making mistake again because they know they are still learning, and it helps them better in communication. Communicative Language Teaching (CLT) is a better promising way of learning English since in which students are practicing English as if they are using it in real situation.Further suggestion is that to make use of this approach in classroom activities and encourages students to actively participate in each activities, whether in classroom or outside the classroom.